2021
DOI: 10.3389/fpubh.2021.680028
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Demographic Determinants of Substance Use and Mental Health During the COVID-19 Pandemic

Abstract: Background: Alcohol consumption and distress have increased among Canadians since the start of the COVID-19 pandemic.Methods: We examined whether sociodemographic and COVID-19-related worries are associated with various combinations of alcohol consumption and comorbid psychological distress variables among a Canadian sample of adults. Data were derived from a sample of Canadian adults (N = 1,005, 49.6% female) who participated in an online survey in May 2020. Four multivariate ordinal logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 71 publications
(77 reference statements)
3
27
0
2
Order By: Relevance
“…( SAMSHA, 2019 ). Distress directly related to COVID-19, as well as the unintended social and economic consequences of lockdowns contributed to increased patterns of substance misuse, along with alcohol- and drug-related overdoses ( Centers for Disease Control and Prevention, 2020a , Czeisler, 2020 , Mougharbel et al, 2021 , Nguyen and Buxton, 2021 ). This was foreseen by many, as stress has long been linked to substance abuse and risk of relapse ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…( SAMSHA, 2019 ). Distress directly related to COVID-19, as well as the unintended social and economic consequences of lockdowns contributed to increased patterns of substance misuse, along with alcohol- and drug-related overdoses ( Centers for Disease Control and Prevention, 2020a , Czeisler, 2020 , Mougharbel et al, 2021 , Nguyen and Buxton, 2021 ). This was foreseen by many, as stress has long been linked to substance abuse and risk of relapse ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jackson ( N = 36,980 adults, 51.0% females) found a significant increase in smoking prevalence, with no gender effect, but a significant increase in high-risk drinking prevalence, with particularly high increases among women ( 40 ). Mougharbel ( 41 ) ( N = 1,005, 49.6% females) found that females had higher odds of increased drinking and anxiety during lockdown. Thompson (2000 adults, 51.9% females) found that while females reported higher rates of emotional distress, significant associations with increased drinking frequency were only observed among males in gender-stratified analyses ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] Some evidences report an increased selling of alcohol during the lockdown period, highlighting the potential increase in substance consumption as well as the worsening of pre-existing substance use disorder or even the risk of relapse of treatment seeking individuals. 19,[32][33][34] Several theoretical, clinical, and empirical contributions pointed out the role of potential explaining variables of the proneness to suffer from problematic alcohol consumption as such as anxiety, depression and stress levels, 35 gender, 36,37 lower age, civil status, high income, fear of COVID-19, finance concerns, 37 using social media as a source of information, experiencing child care challenges, and not being associated with a religious community. 38 As a whole, current literature provided convincing pieces of evidence documenting the impact of the COVID-19 on the propensity to experience both PTSD symptoms and alcohol use disorder.…”
Section: Introductionmentioning
confidence: 99%